OPTIMASI BANDWIDTH MENGGUNAKAN STUB MATCHING IMPEDANSI PADA RANCANG BANGUN ANTENA MONOPOLE ULTRA-WIDEBAND - Darsono, M; Radiansyah, Farid Ahmad (Jurnal Teknologi Terapan, 2024)
The microstrip monopole antenna design study was developed to support Ultra-Wideband (3.1GHz-10.6 GHz) wireless communication technology. This research aims to obtain a minimalist antenna prototype with the ability to operate in the UWB frequency region. Bandwidth optimization is carried out to increase data speed access capacity in wireless communications. The antenna design has two structures in the conductor layer of the RT DUROID 5880 type substrate material. The surface layer structure is a square patch with a transmission line and an impedance stub. For the bottom layer of the substrate, a structure forms the DGS technique. The simulation method is carried out on the antenna design to obtain parameters, such as bandwidth return loss -10dB is 1.29 (fractional) or 9700MHz (absolute) and bandwidth measurement results (absolute) (12,800 MHz-absolute), VSWR (1:2), input impedance at the 3.8GHz frequency (Zin=31.23Ω-j4.12Ω), and the 13.6GHz frequency (Zin=62.93Ω+j28.4Ω). For radiation polarization, the beam width is 116 degrees and the directional strength (Gain) value is 3.15dBi. The entire antenna has the performance characteristics of operating in the Ultra-Wideband spectrum at C-band, X-band and Ku-band frequencies. Omnidirectional polarization, vertical linear polarization, and low gain and minimalist support communication devices.